2008
DOI: 10.1007/s12245-008-0066-7
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department utilization by HIV-positive adults in the HAART era

Abstract: BackgroundNo published study has analyzed emergency department (ED) utilization by human immunodeficiency virus (HIV)-positive adults in the highly active antiretroviral therapy (HAART) era.AimsThe purpose of this study is to describe the demographic and HIV-specific variables associated with ED utilization by HIV-positive adults and their diagnoses when discharged from the ED or subsequently from the hospital.MethodsWe conducted a retrospective cohort study of all HIV-positive adults cared for at a tertiary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The ICD-9 Diseases/Injuries Tabular Index has been used in previous studies to analyze the characteristics of ED and hospital discharge diagnoses in HIV-positive patients. 28-29 All statistical analyses were performed using SAS 9.1 (SAS, Cary, NC). All p -values are two-sided.…”
Section: Methodsmentioning
confidence: 99%
“…The ICD-9 Diseases/Injuries Tabular Index has been used in previous studies to analyze the characteristics of ED and hospital discharge diagnoses in HIV-positive patients. 28-29 All statistical analyses were performed using SAS 9.1 (SAS, Cary, NC). All p -values are two-sided.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, in contrast to studies examining inpatient and out patient health care use, [2][3][4][5][6] comparatively few contemporary studies exist examining emergency department use among people with HIV. [7][8][9][10][11] Studies conducted in the years pre ceding the introduction of combination antiretroviral ther apy demonstrated that people with HIV had rates of emer gency department visits that were three to fourfold higher than those of the general population. 12,13 Although subse quent studies found persistently heightened rates of emer gency department use following the introduction of com bination antiretroviral therapy, inferences were limited by samples that were small and not populationbased.…”
mentioning
confidence: 99%
“…12,13 Although subse quent studies found persistently heightened rates of emer gency department use following the introduction of com bination antiretroviral therapy, inferences were limited by samples that were small and not populationbased. 7,9,10 A recent analysis of the US National Hospital Ambulatory Medical Survey demonstrated that rates of emergency department visits among people with HIV continue to exceed those of noninfected people (633 v. 438 visits per 1000 people), although by a smaller magnitude than during the preceding decade. 14 Analogous populationbased studies characterizing emer gency department use among people with HIV in a Canadian setting are lacking.…”
mentioning
confidence: 99%
“…The growing number of people living longer with HIV has brought to light new issues regarding the cumulative effects of living many years with the virus. Particularly, the social-structural challenges experienced by many chronically ill populations—poverty, housing instability, food insecurity, addictions and mental health comorbidities—exacerbate existing health issues and have been shown to contribute to frequent ED use (Betz et al, 2005; Hunt, Weber, Showstack, Colby, & Callaham, 2006; Knowlton et al, 2001; Kushel, Gupta, Gee, & Haas, 2006; Masson, Sorensen, Phibbs, & Okin, 2004; Tashima et al, 2001; Venkat, Shippert et al, 2008), as have psychosocial issues related to lack of support, stigma, marginalization, loneliness and distress (Bernstein, 2006; Dunlop, Coyte, & McIsaac, 2000; Geller, Janson, McGovern, & Valdini, 1999; Koziol-McLain, Price, Weiss, Quinn, & Honigman, 2000; Lowe et al, 2005; Mandelberg, Kuhn, & Kohn, 2000; Padgett & Brodsky, 1992). …”
Section: Introductionmentioning
confidence: 99%
“…In order to improve care for vulnerable populations and to optimize allocation of resources, it is critical to better understand the drivers of frequent and non-urgent ED use. Following the same line of inquiry as previous studies (Fairbairn et al, 2011; Venkat, Shippert et al, 2008), the objective of this analysis was to describe the factors associated with frequent and non-urgent ED use in a cohort of hard-to-reach HIV positive individuals on ART using St. Paul’s Hospital in downtown Vancouver, British Columbia (BC).…”
Section: Introductionmentioning
confidence: 99%